Sailing Toward Sustainable Horizons: A Case Study of a Solar-Powered Boatyard's Business Model Canvas - Muhammad Usman Sikandar (INOVTEK POLBENG, 2024)
This study presents an in-depth analysis of the business model canvas proposed for a pioneering solar-powered boatyard (Koshi, Nepal). The case study delves into the strategic framework, organizational structure, and operational methodology of the boatyard, highlighting its innovative approach in the maritime industry. Emphasizing the development of Solar Hybrid boats, the boatyard integrates cutting-edge technology and sustainable practices to offer vessels that redefine industry standards. The abstract discusses pivotal components of the business model, from strategic partnerships to resource allocation, and customer segments, all visualized within the Business Model Canvas. The study explores the competitive edge gained through innovative technologies, value propositions, and the market feasibility underlying the business strategy. Additionally, the analysis discusses the boatyard's market expansion opportunities, potential risks, and mitigation strategies, reflecting its position at the forefront of the solar boat market. Through visual representation and analysis, this article provides a comprehensive exploration of the business canvas, serving as a navigational guide for the maritime industry's transition toward sustainable and innovative practices.